HIV-1 strain-specific neutralizing antibody responses and the dynamics of viral evolution - Majara, Lerato Charlotte (Department of Clinical Laboratory Sciences, 2018)
It is widely held that for an HIV-1 vaccine to provide sterilizing immunity, it would need to elicit broadly neutralizing antibodies (bnAbs). However, factors underlying the development of these antibodies are not clear. There is evidence to suggest that in some individuals who develop bnAbs, the development of breadth is influenced by the co-evolution of the transmitted/founder (t/f) virus and earlier strain-specific neutralizing antibody (ssnAb) responses. Here we characterized the viral evolution, ssnAb and bnAbs responses in CAP292, an HIV-1 infected woman who developed bnAb responses from one year post infection. We used single genome amplification (SGA) to characterize viral evolution at four time points: at acute infection; after the development of strain-specific neutralizing responses; at the first detection of the broadly neutralizing antibody response; and lastly, at the peak of the broad response. We identified the t/f virus, and generated chimeric viruses from this to determine the targets of the ssnAb responses. A panel of site-directed mutant viruses were used to map the specificity of the bnAb responses. Our data indicated that infection was most likely founded by a single virus and that the first wave of ssnAbs emerged at 14 weeks post infection (w.p.i), targeting the V1V2 loop of Envelope (Env). A second wave of ssnAbs, possibly targeting the C3V4 region, emerged by 30 w.p.i. Two distinct viral clusters were detected by the time the bnAb response peaked, suggesting the presence of distinct escape pathways. Mapping of the bnAb specificities indicated that CAP292 produced PGT128-like bnAb responses targeted toward the 332 glycan.